Service Quality Assessment of Hospitals in Asian Context: An Empirical Evidence From Pakistan. (21st June 2017) - Shafiq, Muhammad; Naeem, Muhammad Azhar; Munawar, Zartasha; Fatima, Iram
Hospitals vary from one another in terms of their specialty, services offered, and resource availability. Their services are widely measured with scales that gauge patients' perspective. Therefore, there is a need for research to develop a scale that measures hospital service quality in Asian hospitals, regardless of their nature or ownership. To address this research need, this study adapted the SERVQUAL instrument to develop a service quality measurement scale. Data were collected from inpatients and outpatients at 9 different hospitals, and the scale was developed using structural equation modeling. The developed scale was then validated by identifying service quality gaps and ranking the areas that require managerial effort. The findings indicated that all 5 dimensions of SERVQUAL are valid in Asian countries such as Pakistan, with 13 items retained. Reliability, tangibility, responsiveness, empathy, and assurance were ranked first, second, third, fourth, and fifth, respectively, in terms of the size of the quality gap. The gaps were statistically significant, with values ≤.05; therefore, hospital administrators must focus on each of these areas. By focusing on the identified areas of improvement, health care authorities, managers, practitioners, and decision makers can bring substantial change within hospitals.